Healthcare workers perceptions in the difficult moment of the end of life and coping strategies adopted during the COVID-19 pandemic: an Italian pilot study - Vitale, Elsa; Conte, Luana; dell'Aglio, Angelica; Calabrò, Antonino; Ilari, Federica; Bardone, Lorenzo; Benedetto, Angelo; Caldararo, Cosimo; Zacchino, Simone; Lezzi, Alessia; Giordano, Martina; Carvello, Maicol; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and Aim of the work. In a society that tries so hard to forget and make people forget that death exists, death has never been so close to man in his daily life as during this pandemic. Health care professionals have therefore all too often had to deal with the death of the people they care for and with related issues such as, for example, the dignity of death, the humanization of death and care for the dying. The aim of the study is to highlight the perceptions of physicians, nurses and health and social workers in the difficult moment of the end of life, also analyzing which coping strategies were implemented by them. Methods. All Italian healthcare workers were enrolled in this survey. The questionnaire was administered in an online version. Physicians, nurses and support staff (social and health workers) were contacted through social networks. Results. A total of 512 healthcare workers were enrolled in this survey. No statistical significant differences were recorded among the COPE-NVI- 25 sub dimensions according to sex, profession and to different wards. Additionally, by considering the COPE-NVI-25 sub dimensions according to years of work experience, a statistical significant difference was reported in the Transcendent Orientation sub dimension (p=.047), as healthcare workers with 11-20 years of work experience recorded higher levels than the other two groups. By considering differences in the COPE-NVI-25 sub dimensions according to religion, significant differences were recorded in the transcendent orientation (p=.032), in the positive attitude (p=.030), in the social support (p=.035). Conclusions. From the evidence in the literature, the quality of end-of-life care performance has a positive correlation with awareness of a good death and attitudes towards end-of-life care.